2010
DOI: 10.1111/j.1750-3841.2010.01815.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Bread Dough with Added Fiber Polysaccharides and Phenolic Antioxidants: A Review

Abstract: During breadmaking, different ingredients are used to ensure the development of a continuous protein network that is essential for bread quality. Interests in incorporating bioactive ingredients such as dietary fiber (DF) and phenolic antioxidants into popular foods such as bread have grown rapidly, due to the increased consumer health awareness. The added bioactive ingredients may or may not promote the protein cross-links. Appropriate cross-links among wheat proteins, fiber polysaccharides, and phenolic anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
1
22

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(193 citation statements)
references
References 150 publications
(266 reference statements)
7
163
1
22
Order By: Relevance
“…Snthetic antioxidants were also often used but most of these antidepressants have several adverse side effects. Consumers' awareness of the health risks of synthetic antioxidants and demand for natural food ingredients has resulted in extensive research on naturally occurring antioxidants (Dua et al, 2015;Iqbal et al, 2007;Sivam et al, 2010). SK contains substantial amounts of phenolic acids, such as, coumaric aicd, caffeic acid, ferulic acid, salicin, epicathechin, tannin, flavonoid, and luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…Snthetic antioxidants were also often used but most of these antidepressants have several adverse side effects. Consumers' awareness of the health risks of synthetic antioxidants and demand for natural food ingredients has resulted in extensive research on naturally occurring antioxidants (Dua et al, 2015;Iqbal et al, 2007;Sivam et al, 2010). SK contains substantial amounts of phenolic acids, such as, coumaric aicd, caffeic acid, ferulic acid, salicin, epicathechin, tannin, flavonoid, and luteolin.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of MFP already in the amount of 2.5% resulted in very large changes in the TPC from 0.88 to 2.12 GAE/g dw. Many authors reported that phenolics can form complexion with protein in matrix, and heating process also may alter phenolic antioxidants in bread during baking in different extents [38,39].…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Gluten proteins play a vital role in bread quality Khatkar 2015a, 2015b;Sivam et al 2010;Dong et al 2009). They affect the stability of the dough and bread volume and form the skeleton of wheat dough.…”
Section: Introductionmentioning
confidence: 99%